Development of a liquid chromatography-tandem mass spectrometry method to determine colistin, bacitracin and virginiamycin M1 at cross-contamination levels in animal feed. Issue 9 (2nd September 2021) - Gaugain, Murielle; Raynaud, Amandine; Bourcier, Sophie; Verdon, Eric; Hurtaud-Pessel, Dominique
ABSTRACT: Cross-contamination of animal feed with antibiotics may occur during manufacturing in feed mills, because shared production lines can be used for medicated and non-medicated feed, but may also occur during transport, storage and at the farm level. This is a major issue in the current context where antimicrobial usage must be controlled in order to maintain their effectiveness. A LC-MS/MS method was developed for the determination of colistin, bacitracin A and virginiamycin M1 in feed for pigs, poultry and rabbits at concentrations similar to those encountered in cross-contamination. After investigating various issues related to colistin behaviour and matrix effects, we successfully validated this method according to the requirements of European regulations in terms of linearity, trueness, precision, limit of quantification and limit of decision. Trueness ranged 88.6–107.8% and precision ranged 12.6–21.2%. We then applied this method to the analysis of medicated pig feed to check the performance of the method on "real" samples of medicated feed. We subsequently analysed non-medicated pig, and rabbit feed samples, collected directly on farms, to check the rate of cross-contamination. No samples were contaminated by colistin, bacitracin, or virginiamycin.